Intermarriage, conflict and social control in Ireland - the decree 'ne temere' - Lee, Raymond M. (Economic & Social Studies, 1985)
The decree `Ne temere? of 1908 by which the Roman Catholic Church has, until recently, governed the marriage of one of its members to someone who is not a Roman Catholic has had attributed to it a number of deleterious consequences. The origins of the decree, as it has applied to Ireland, are described, as are the events following its promulgation which came to be referred to as the `McCann case?. It is argued that the McCann case can be thought of as a `moral panic?.
Keywords: Marriage - Ireland; Intermarriage - Ireland